Pengaruh Prosentase Pemberian Pakan Terhadap Kelangsungan Hidup Dan Laju Pertumbuhan Udang Vannamei (Litopenaeus vannamei) [The Effect Of Feed To Survival And Growth Rate Of Vannamei Shrimp (Litopenaeus vannamei) ] - Nuhman Nuhman (Jurnal Ilmiah Perikanan dan Kelautan, 2009)
AbstractFeed is an important factor in the culture of vannamei shrimp. The optimum feed have clone to prevent underfeeding or overfeeding, whereas the amount of feed must have adjust with shrimp biomass. The aim this research is to know the percentage of optimum feed from vannamei shrimp. The method is experimental research with Complete Random Design, and the result showed that difference of percentage of feed is not significantly for daily growth of vannamei shrimp. The amount of feed as mush as 40 % of biomass weight/day showed the best daily growth (9.86 %).